Analysis of DNA Fragment Obtained from Groupers (Epinephelus fuscoguttatus) Challenged by Vibrio alginolyticus - St Hidayah Triana (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
The objective of this study was to analyse the size of DNA fragment from both resistant and susceptible groupers (Epinephelus fuscoguttatus) after infection by Vibrio alginolyticus. This study was conducted by two steps, firstly, determination of Lethal Concentration (LC50) of Vibrio alginolyticus to obtain fish which resistant and susceptible against Vibrio alginolyticus infection. Secondly, analysis of DNA fragment from both resistant and susceptible fish against Vibrio alginolyticus infection by PCR-RAPD method. In order to analyse the fragment of DNA from the fish, DNA was extracted and the concentration was counted using Kit. Sixteen primers were used, which six primers (RAPD 1-6) were from RAPD Kit, other primers were OPA-14, -A, -B, -C, and -D, YNZ 22, UBC-122, -158, -456, and -457. The results demonstrated that the concentration of bacteria that caused 50 % of fish mortality (LC50)was 7.4 × 105 CFU/L. Based on this concentration, the number of fish which were resistant and susceptible against Vibrio alginolyticus infection were obtained. For the DNA fragment analysis, the concentration of DNA after extraction ranges from 448 μg/ml to 3320 μg/ml with the purity ranges from 86-95 %. From 16 primers used for PCR-RAPD, only 6 primers showed DNA fragments in the gel electrophoresis. Those primers are OPA-14, YNZ 22, UBC-122, -158, -456, and -457. The number of DNA fragments was higher in the group of resistant fish (average 6.4 fragments) than in the group of susceptible fish (average 4.9 fragments). Fifty seven percent (57%) from resistant fish showed specific DNA fragments with size 2.0 kb, indicate that these fragment sizes have a potential role to be used as a marker for obtaining the resistant fish against bacterial infection.